Parametric spectral inversion of seismic source, path and site parameters: application to northeast Italy. Issue 3 (10th November 2022) - Cataldi, Laura; Poggi, Valerio; Costa, Giovanni; Parolai, Stefano; Edwards, Benjamin
SUMMARY: Strong ground motion prediction is a fundamental topic in the field of engineering seismology, as it provides the input for seismic hazard studies as well as for vulnerability and risk assessment. The spectral modelling approach can provide a realistic representation of ground motion behaviour, possibly including its frequency variability, as the full ground motion spectrum is modelled analytically. In its parametric form, this approach requires a careful calibration of the model, starting from empirical observations and fitting the source, path and the site-specific response assuming a predefined physically constrained functional form. This study explores the use of spectral modelling for a study area in northeast Italy, at the border with Slovenia and Austria. It is based on the parametrization of seismic source and attenuation effects, and it also allows to estimate site effects, as a by-product. The main innovation with respect to standard spectral modelling is the inclusion of dedicated uncertainty estimators in the functional form. Parametric inversion of source and path attenuation is performed on a data set corresponding to 23 events recorded by 24 stations located within the target area. The modular inversion setup allows to properly include a priori constraints in the mathematical solution to reduce trade-off between variables. Spectral amplification at each site is defined with respect to the network average rock condition, and its frequency-dependent component is estimated from residual analysis after the inversion. Inverted source parameters are comparable with reference values for the region available from literature (with seismic moments between 10^13 and 10^15 N·m, and related stress drop values in the range 1.5 - 15.5 MPa ); the same is also true for average attenuation properties (e.g. apparent frequency-independent attenuation quality factor Q_0 of 1145 ). For a selection of stations with available characterization based on different methods, a preliminary comparison of site-specific response functions shows that both the frequency value and amplitude of the main amplification peaks are well recovered. These encouraging results open to the possibility of subsequently using the calibrated model for forward modelling purposes.